THE DEVELOPMENT OF THAI READING ALOUD SKILLS THROUGH GAME-BASED LEARNING COMBINED WITH SKILL EXERCISES FOR GRADE 2 STUDENTS AT BAN KHANGPHIBAN SCHOOL, MAE SOT DISTRICT, TAK PROVINCE - Udomsin, Nanthikorn; Tajanun, Perasak; Manava, Wilai; SuKKasem, Sopa (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2025)
The purposes of this research were to: 1) study the effectiveness of a game-based learning plan combined with reading skills exercises in developing Thai language reading skills of Prathomsuksa 2 students at Ban Khang Phiban School, Mae Sot District, Tak Province to meet the efficiency criterion of 80/80 2) comparison the achievement on the subject of Thai language of Prathomsuksa 2 students before and after studying using game-based learning method. The sample consisted of Prathomsuksa 2 students 23 samples in 1 class. The research instrument consists lesson plans and achievement tests. the methods of statistics are implemented in this research – mean, percentage, standard deviation and t-test dependent sample. The results found that: 1) The effective of the game-based learning plan combined with reading skill exercises in developing Thai language reading skills of Prathomsuksa 2 students can significantly increase the efficiency in developing the students' reading skills. The average score before learning was 54.34 and after learning increased to 90.20, which is higher than the specified criteria (80/80). 2) The academic achievement of students who organized learning activities using games as a base with reading aloud skills exercises before learning found that the average was 10.87 and after learning, the average was 18.04 was higher than before the learning management was statistically significant at the .05 level different.